Contrasting Antibacterial Capabilities of the Surface Mucus Layer From Three Symbiotic Cnidarians - Rivera-Ortega, Jacqueline; Thomé, Patricia E. (Frontiers in Marine Science, 2018)
Coral reefs are affected by the deterioration of the oceans due to global warming and other anthropogenic perturbations, increasing the frequency and severity of bleaching and disease. To overcome some of these conditions, reef corals and other cnidarians rely on a mucus layer housing a diverse community of beneficial microorganisms and mechanisms of innate immune response. The antimicrobial defense has been associated with the bacterial community in these organisms, but the potential antimicrobial activity of the mucus layer itself has not been explored fully. We hypothesized that the bacteria-free mucus layer of different cnidarians would show differential and specific antimicrobial and immunological responses when challenged with two potentially pathogenic bacteria. We evaluated this capability through antimicrobial properties, immune response and biochemical composition of the mucus. Results clearly showed that the mucus of healthy cnidarians has the capability of inhibiting the growth of Serratia marcescens and Aurantimonas sp. in a species-specific way that includes differences in the potency of the response. The anemone Exaiptasia pallida was particularly potent against Aurantimonas sp. while the coral Pseudodiploria strigosa and the medusa Cassiopea xamachana had similar capabilities against both bacterial strains. In coral affected by black band disease, this antibacterial capability diminished in the mucus layer, but the associated bacteria remained potent. Results showed that hydroxyproline and phenoloxidase increased in the transition zone of diseased corals, although melanin was not detected in any of the animals tested. Bleaching of anemones and medusas also diminished the antibacterial capability of the surface mucus layer, but in anemones, the associated bacteria did not show a significant reduction in their ability to inhibit the growth of the bacterial strains. The mucus of bleached medusas showed an increased inhibitory activity against Aurantimonas sp. that may be associated with a specific bacterial strain we isolated. Mucus collected from bleached anemones and medusas did not show a significant immune response. In this work, we show that the surface mucus layer itself has antibacterial properties not associated with the bacteria this layer houses; such properties diminished due to disease or bleaching, while immunological responses increased in the mucus of diseased animals.